Vitamin B12 Production by Lactobacillus Species Isolated from Milk Products - Singh, Brajeshwar; Sharma, Shruti (Journal for Research in Applied Sciences and Biotechnology, 2022)
An investigation entitled “Studies on production of Vitamin B12 by Lactobacillus species isolated from milk products” was conducted in the Division of Microbiology, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, to study the capability of mutants generated out of UV and EMS mutagens of native Lactobacillus isolates, for Vitamin B12 production potential. In this study 8 isolates of Lactobacillus were isolated from curd and kaladi. Screening and Quantification of isolates was done on Vitamin B12 assay medium. The Vitamin B12 production by Lb-7 was 0.39 mg/g DCW. Lb-7, the fastest growing strain was selected for strain improvement, that was done by UV and EMS mutagens. Based on performance during screening, UV mutant was taken up for fermentation optimisation studies. The Vitamin B12 production by UV mutant was 0.63mg/g DCW. Three fermentation parameters i.e temperature, pH and inoculum load were optimized for mutant to enhance Vitamin B12 production. The Vitamin B12 production at 25°C was 2.05 mg/g DCW, 5.5 pH was 1.55mg/g DCW and 108 inoculum load was 1.53mg/g DCW. Best results were recorded at 25°C, 5.5 pH and 108 cfu/ml of microbial load. An increase in temperature, pH and inoculum load caused decrease in Vitamin B12 production due to death of cells.